Differential effects of a reading strategy intervention program for migrant children in migrant schools in China - Guo, Qian; Kim, Young-Suk; Liu, Yan; Peng, Yan; Sun, Wenkai; Yan, Jin; Yang, Li (Frontiers in Education, 2023)
There are over 14 million migrant children in the compulsory education system in China and the number has been increasing rapidly. However, the quality of education in schools for migrant children is often poor. Meanwhile, numerous studies indicated the importance of reading skills developed by the end of third grade. Few studies, however, have investigated the early reading development of migrant children in migrant schools in China. In the current study, we examined the effects of training Chinese language arts teachers in supporting the reading of migrant children in migrant schools with a randomized control trial design. A total of 1679 students from 47 third-grade classes in 13 migrant schools for migrant children in Beijing, China, participated in the study. The intervention was composed of teacher professional development in reading instruction and the teachers’ in-class instruction on independent reading. Students in both treatment and control conditions received books for independent reading. The program improved the students’ overall reading performance, particularly on inferential comprehension and for students who did not live in Beijing before starting elementary school (which we speculate captures the degree of family mobility and the rural-urban gap in the access to educational resources). The results suggest a potential way to promote the reading development of migrant children in migrant schools in China.